Public art and right to the city: the meeting of art with the slums of contemporary Rio de Janeiro (Tempo e Argumento, 2009)
The issue of this paper are the urban images in the field of the public art. The study characterizes how public sculpture of monumental logic lost relevance with the social changes in contemporary Brazil. In general, we could say that the strugle for the right to the city redefined the role of the urban images. In our days, public art in the city participates in the affirmation of urban identities, local powers and communitarian forces. In this context art and ‘favela’ meet each other in the city of Rio de Janeiro.
Keywords: urban images; public art and sculpture; city and urban communities